PENGARUH PERMAINAN DAKON GEOMETRI TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK USIA 4-5 TAHUN DI PAUD DAHLIA MANDIRI DESA MUNTAI KECAMATAN BANTAN KABUPATEN BENGKALIS - Lili Artika; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations of the ability to know the geometry of the students have not developed optimally. So that should be the application of geometry dakon game against the ability recognize geometric shapes. This study aims to determine the effect of applying geometry dakon game against the ability to know the geometry of children aged 4-5 years in early childhood Dahlia Mandiri Muntai Village, District Bantan Bengkalis. This type of research is the experiment with one group pretest and posttest design. Sampel used in this study 20 students. The data collection techniques were used that observation sheet. Data were analyzed using t-test using SPSS 17.0. Based on test results obtained hypothesis t = 12.931 with Sig = 0,000 table = 1.729, for ttest > ttable with sig level 0.05. Then Ho is rejected and Ha accepted which means there is a very significant difference between before and after the game Dakon geometry. Most of the game dakon geometry influence on the ability to know the geometry of children aged 4-5 years in early childhood Dahlia Mandiri Muntai Village Bengkalis Bantan District is 51.64%. Key Words : Ability Shape Geometry, Geometry Dakon